Determinants of Health-Related Quality of Life Among Community-Dwelling Thai Older Adults in Chiang Mai, Northern Thailand - Aung TNN; Moolphate S; Koyanagi Y; Angkurawaranon C; Supakankunti S; Yuasa M; Aung MN (Dove Medical Press, 2022)
Thin Nyein Nyein Aung,1,2 Saiyud Moolphate,3 Yuka Koyanagi,4 Chaisiri Angkurawaranon,1,2 Siripen Supakankunti,5 Motoyuki Yuasa,6,7 Myo Nyein Aung6- 8 1Department of Family Medicine, Faculty of Medicine, Chiang Mai University, Chiang Mai, 50200, Thailand; 2Global Health and Chronic Conditions Research Group, Chiang Mai University, Chiang Mai, 50200, Thailand; 3Department of Public Health, Faculty of Science and Technology, Chiang Mai Rajabhat University, Chiangmai, 50300, Thailand; 4Department of Medical and Health Science, Tokyo Ariake University, Tokyo, 135-0063, Japan; 5Centre of Excellence for Health Economics, Faculty of Economics, Chulalongkorn University, Bangkok, 10330, Thailand; 6Department of Global Health Research, Graduate School of Medicine, Juntendo University, Tokyo 113-8421, Japan, and; 7Faculty of International Liberal Arts, Juntendo University, Tokyo, 113-8421, Japan; 8Advanced Research Institute for Health Sciences, Juntendo University, Tokyo, 113-8421, JapanCorrespondence: Myo Nyein Aung, Department of Global Health Research, Graduate School of Medicine, Juntendo University, Tokyo, 113-8421, Japan, Email myo@juntendo.ac.jpBackground: Population aging has been growing worldwide and Thailand has become an aged society with 20% of its population aged 60 and over. Age-related decline in physical and mental health impacts the health-related quality of life (HRQOL) of older adults.Purpose: We aimed to describe the HRQOL of Thai older adults, residing in the community.Methods: This cross-sectional survey was part of a Community-Integrated Intermediary Care project (CIIC), TCTR20190412004. A total of 1509 participants from an intervention arm of a cluster randomized controlled trial were included. A Thai version of the Euro-Qol questionnaire (EQ-5D-5L) was used to determine the HRQOL and associated sociodemographic background, health behaviors and underlying diseases of a representative sample from Maehia, Chiang Mai, Thailand. SPSS version 24 was used to analyze data via descriptive analysis and binary logistic regression.Results: The mean age of the participants was 69.31± 7.10 years, and nearly a quarter (23.8%) was older than 75 years. The mean EQ index score was 0.81± 0.23 and older age, lower educational attainment, unemployment, lack of exercise habits, current smokers, having history of a fall in the last 6 months, diabetes, hyperlipidemia, dependency assessed using Barthel's Activity of Daily Living (ADL) Index, and depression using the Geriatric Depression Scale (GDS) were more likely to represent HRQOL-related problems.Conclusion: Our findings have highlighted the factors affecting the HRQOL of community-dwelling older adults which could be of importance in preparing for active and healthy aging communities. The routine dependency assessment using the ADL index will be useful in estimating the HRQOL of the aging population. Fall prevention programs are also recommended to reduce dependency. Moreover, the association of having diabetes and hyperlipidemia with problems in HRQOL dimensions highlight the need for public health intervention not only to prevent the increasing burden of non-communicable diseases but also to improve the HRQOL of older adults.Keywords: aging, Community-Integrated Intermediary Care, CIIC, health-related quality of life, HRQOL, Thailand